Infinitely many fast homoclinic solutions for some second-order nonautonomous systems - Yang, Liu; Luo, Liping; Luo, Zhenguo (Український математичний журнал, 2014)
We investigate the existence of infinitely many fast homoclinic solutions for a class of second-order nonautonomous systems. Our main tools are based on the variant fountain theorem. A criterion guaranteeing that the second-order system has infinitely many fast homoclinic solutions is obtained. Recent results from the literature are generalized and significantly improved.